Covid-19 impact on the international sport organizations´ activities - Kokhanska, S. (University of Peloponnese, 2022)
The purpose of this study is a deep analysis of the activities of sports organizations in the context of the COVID-19 pandemic. The main tasks that were solved during the study were to determine the conditions of functioning of sports organizations during the COVID-19 pandemic. An important step of the research was to identify the challenges that various sports organizations are facing in relation to the worldwide pandemic. The next step of the study was to define the effective ways of solving the problems of functioning. A review of the existing bibliography was carried out regarding the operation features of the Olympic system components as well as the impact of the COVID-19 pandemic on various sports organizations, including the IOC, ISFs, NOCs and others. Further, the study was conducted through interviews with 92 experienced sports professionals. The results of the interviews helped to create a questionnaire based on the received information. Through the questionnaire, the information about main problems in the functioning of sports organizations during the COVID-19 pandemic were identified. Moreover, based on the results of the survey, effective ways of solving the arisen problems were identified. The results of the study showed that the COVID-19 pandemic has a significant impact on the activities of the vast majority of sports organizations. The main problems faced by the organizations were the inability to hold sports competitions, the lack of developed and effective online platforms and the deterioration of communication between representatives of the organization. According to the results of the study, the main ways to solve the arisen problems are the improvement of existing and the creation of new additional online platforms, the expansion of cooperation with other national and international institutions, the creation of new formats for holding national and international competitions.